INDONESIA HAS RATIFIED THE ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION: WILL THE HAZE DISAPPEAR? - Sambodo, Maxensius Tri (RIEBS, 2015)
Land and forest fires and haze have become one of the biggest environmental challenges in the ASEAN region. Indonesia has become the major source of transboundary haze in the region. By mid-September 2014, Indonesia had ratified the ASEAN Agreement on Transboundary Haze Pollution (AATHP). This paper makes two major contributions: first, the paper quantitatively revisits the causes of hotspots in Indonesia; and second, the paper identifies and discusses the national efforts that have been made and policy handicaps that need to be removed. The government needs to focus on rehabilitating critical land, promoting reforestation, and protecting peatland ecosystems. Although there is a trend for the number of hotspots to decline, there are no guarantees that transboundary haze can be eliminated. There is hope that by ratifying the AATHP, Indonesia can have better resources to conduct preventive, mitigating and monitoring activities, but there is a need to develop streamlined coordination, law enforcement, and capacity building at national and local level that can promote common interests in fighting the haze, and land and forest fires.